PROCAMPO: FIELD EDUCATION POLICY - Marilene santos; Andréa Rosana Fetzner (Universidade Federal de Sergipe, 2019)
PROCAMPO: FIELD EDUCATION POLICY               Abstract: The article integrates researches that focus on the analysis of the Field Education policy as an alternative to improve the quality of education and contribute to the development of rural areas, it also discusses the Field Education as public policy and its implementation through specific programs. The empirical material analyzed is the Programme of Support to Field Higher Education Degree 'Procampo/Pronacampo'. The analysis focuses in reflecting on the history and definition of concepts in the discussion of Field Education by social movements forefront State bodies represented by the Ministry of Education. In addition, it also discusses Procampo as a significant action of implementation and expansion of Field Education as part of teacher training. The conclusions highlight advances in this implementation; it considers Procampo as an innovation in teacher training, however, to ensure the public policy challenges ahead and a long way by conflicts and clashes of intermingled divergent interests. Key words: Field Education - Public Policy - Procampo